Manipulation in root-associated microbiome via carbon nanosol for plant growth improvements - Lingtong Cheng; Jiemeng Tao; Peng Lu; Taibo Liang; Xutao Li; Dong Chang; Huan Su; Wei He; Zechao Qu; He Li; Wenjun Mu; Wei Zhang; et al. (Journal of Nanobiotechnology)
Abstract Background Modulating the microbiome with nanomaterials has been proposed to improve plant growth, and reduce reliance on external inputs. Carbon Nanosol (CNS) was attracted for its potential to improve plant productivity. However, the mechanism between CNS and rhizosphere microorganisms remained largely elusive. Results Here, we tried to systematically explore the effects of CNS (600 and 1200 mg/L by concentration) on tobacco growth, soil physical properties, and root-associated microbiome. The influence of CNS on soil physicochemical properties and plant growth was significant and dose-dependent, leading to a 28.82% increase in biomass accumulation by 600 mg/L CNS. Comparison between the CNS-treated and control plants revealed significant differences in microbiome composition, including 1148 distinct ASVs (923 bacteria and 225 fungi), microbiome interactions, and metabolic function of root-associated microbiomes. Fungal and bacterial communities had different response patterns for CNS treatment, with phased and dose-dependent effects, with the most significant changes in microbial community structure observed at 1200 mg/L after 10 days of treatment. Microbial networks of CNS-treated plants had more nodes and edges, higher connectivity, and more hub microorganisms than those of control plants. Compared with control, CNS significantly elevated abundances of various bacterial biomarkers (such as Sphingomonas and Burkholderia) and fungi biomarkers (including Penicillium, Myceliophthora, and Talaromyces), which were potential plant-beneficial organisms. Functional prediction based on metagenomic data demonstrated pathways related to nutrient cycling being greatly enriched under CNS treatment. Furthermore, 391 culturable bacteria and 44 culturable fungi were isolated from soil and root samples. Among them, six bacteria and two fungi strains enriched upon CNS treatment were validated to have plant growth promotion effect, and two fungi (Cladosporium spp. and Talaromyces spp.) played their roles by mediating volatile organic compounds (VOCs). To some extent, the driving and shaping of the microbiome by CNS contributed to its impact on plant growth and development. Conclusion Our results revealed the key role of root-associated microbiota in mediating the interaction between CNS and plants, thus providing valuable insights and strategies for harnessing CNS to enhance plant growth. Graphical Abstract